THE ROLE OF MOSQUE TAKMIR IN IMPROVING RELIGION AND MODERATION OF PUBLIC RELIGION: A CASE STUDY AT THE PAMEKASAN FISABILILLAH MOSQUE, MADURA - Jailani, Mohammad (TOLERANSI: Media Ilmiah Komunikasi Umat Beragama, 2024)
The decline in the sense of respect and religious tolerance for the community in Pasean Village, Pamekasan Regency, is related to differences in understanding and differences in beliefs that have created a split in social solidarity in the Pasean area. This was driven by differences in understanding between NU and Muhammadiyah understandings. This study aims to analyze the community and the congregation of the Fisabilillah mosque with the nuances of the concept of moderation in religious moderation, as initiated by the Ministry of Religion led by the Minister of Religion, namely Yaqout Qomas as a bridge for harmonization and tolerance for peace and harmony in Pasean Pamekasan village. The circulating cases are in the Pasean location, Pamekasan, Madura, namely at the Fisabilillah mosque. The research subjects consisted of the local community, community leaders, mosque imams, Fisabilillah mosque congregation and the younger generation. The research method is case study based, meaning that this research is addressed to the public and the academic community. Data collection techniques were carried out by observation and direct interviews with informants and research subjects. Data analysis was performed by display, reduction and data verification. The research results obtained include; consists of specific and general mosque duties. The function of the mosque specifically is devoted to programs of religious moderation activities such as mosque congregations, the local community, and the younger generation are given insight into religious tolerance. Such as activities that lead to moderate activities, tawasuth, mutual respect in every difference, tawazun, the community is directed to help each other indiscriminately in each other. As for the general program of activities focused on mosque takmir for the younger generation, students and students in pasean, Pamekasan detailed researchers, among others: First, the progress and prospects for work programs for mosque youth activities have increased significantly as those accompanied by mosque takmir Second, takmir efforts the mosque involves RISMA (mosque youth) in every religious activity, involves teenagers in every Ramadan activity, Third, Activities that support mosque activities are inseparable from the role of the mosque in collaboration with the local community such as mutual cooperation, making study schedules, Friday sermons 'at and monthly recitations organized by the takmir of the mosque. Fourth, as an obstacle to mosque activities, there is a lack of awareness from parents regarding religious values and religious tolerance. What is really striking is the difference in understanding between NU and Muhammadiyah, which is why the younger generation, mosque youth, and mosque congregations sometimes follow it. Fifth, the alternative provided by the takmir of the mosque is providing training, spiritual studies that lead to religious moderation, anti-corruption training, and working with nearby campuses in Pamekasan, such as IAIN Madura, UNIRA (University of Madura), UIM ( Madura Islamic University), and STIT Al-Khairat Pamekasan). Each campus provides KKN or community service program activities which encourage takmir mosques and mosque youth to be aware of religion, worship, spirituality, and society related to religious moderation activities and tolerance for religious harmonization, especially in understanding similarities and differences in understanding. This mosque-based research has contributed to the harmonization of villages and villages in Pamekasan in the outcome of the religious moderation policy launched by the Ministry of Religion.